Penerapan Asas In Dubio Pro Natura Terhadap Perlindungan Dan Pengelolaan Lingkungan Hudup di Indonesia - Stevi Inria Sagal, febritisia (Jurnal Ilmu Hukum Reusam, 2023)
Indonesia's environmental land condition and quality index in 2021 has increased by 1.18 points compared to 2020 with 50.9% of the land area, it shows the condition of the land area is getting better and the priority of stakeholders to apply the In Dubio Pro Natura principle will further support the sustainability of environmental functions. The regulation of the In Dubio Pro Natura principle in Law No. 32 of 2009 is very important to be enforced in Indonesia as an effort to maintain environmental sustainability and anticipate environmental damage. This research uses normative juridical method by using literature study or documentary study of legal materials in answering the legal issues at hand. When environmental damage is irreversible, judges must prioritise environmental protection and restoration in environmental cases in applying the principle of In Dubio Pro Natura with the expectation that the results of their decisions can promote and benefit nature through concrete actions taken by the defendants in court decisions.